Isolation and screening of potential bacteriophages for inhibition of Pseudomonas spp. from shrimp’s samples - Tran, Xuan Thien Phi; Nguyen, Pham Anh Thi; Banh, Chi Hai; Truong, Thi Bich Van (Vietnam Journal of Biotechnology, 2025)
Pseudomonas spp. are significant bacterial pathogens in farmed shrimp, causing substantial economic losses in aquaculture. This study investigated the potential of bacteriophages to control Pseudomonas spp. isolated from shrimp. Eight Pseudomonas spp. isolates were screened against 28 bacteriophage strains to determine their host range. Bacteriophage strains ΦXP4.1, ΦXP2.1, and ΦXP2.2 were selected for further analysis, including plaque assays and biofilm experiments, due to their ability to infect several Pseudomonas spp. isolates. All three phages effectively infected Pseudomonas sp. VCST7 and reduced bacterial density. Notably, ΦXP4.1 demonstrated the highest efficacy, reducing bacterial density by 11.08% and biofilm biomass by 66.3%. Transmission electron microscopy revealed that ΦXP4.1 belongs to the class Caudoviricetes, with an average head diameter of 61.301 nm and an average tail length of 135.7 nm. These findings suggest that bacteriophages, particularly ΦXP4.1, hold promise as biocontrol agents against Pseudomonas spp. in aquaculture.